Description of Shrimp Consumption Contains Chlorine to Gastrointestinal Health Effects among Sub Contract Workers in Company X - Shofiyatur Rohmah; Lilis Sulistyorini (Universitas Airlangga, 2017)
One type of chlorine that is commonly used in industry is sodium hypochlorite. Sodium hypochlorite is not included into one of permitted food additives because it can cause of health effects such as burns of the mouth and throat, gastrointestinal irritation, nausea, vomiting, and diarrhea. This research was purpose to analyze the description of shrimp consumption containing chlorine and gastrointestinal health effects in sub contract workers's in Company X's sub contract worker. This study was used cross sectional as design study with descriptive analysis. Sample was determined by using total population of 9 workers. The level of chlorine in shrimp was measure in the Environmental Health Laboratory, Public Health Faculty of Universitas Airlangga. Worker characteristics and gastrointestinal health effects had been known by questionnaires. The results of chlorine test in shrimp were positive and the largest residual levels were 1.5 ppm. Result showed that 77.8% of respondents had low category of gastrointestinal health effects and 22.2% of respondents had moderate category of gastrointestinal health effects. It can be concluded that gastrointestinal health effects were higher in sub contract workers with low category, at age 35–44 years old with 4–14 years of working experience, has been 9–23 years consuming shrimp that boiled 2 times with clean water, frequency of consumption is 4–7 times each month and volume of each consumption is 0.5–1.05 grams. Workers should eliminate their habit of consumption chlorinated shrimp at X Company, while X company should reinforce the regulation with sanctions related eating shrimp which exposed by chlorine.